THE EFFECTS OF COMMUNICATION TECHNOLOGY ON THE COMMUNITY RELIGIOUS LIFE IN ACEH SINGKIL REGENCY - Syahminan Syahminan Syahminan (State Islamic University of North Sumatra Indonesia, 2017)
This study aims to discover the effects of communication technology on the community religious life in Aceh Singkil regency. The research focuses on how are the positive impacts of using communication technology derived by the community religious life in this regency, and also its negative impacts regarding this point of view. This is descriptive qualitative research which is provided with no number at all. The participation and observation method are used in this inquiry to find out the real data from participant in the object of research area. As a findings, In fact, sometimes many parents who do not have time for their children, many parents who work day and night and do not pay attention to how his son. They only think that the important thing to have a lot of money so that all the needs of their children can be met, even many of them who give very much money to their children, so that his son can waste money to buy these communication technology goods. Furthermore, Responsibility in teaching emphasizes teachers' duty in planning and implementing instruction. In this task, teachers are required to have a set of knowledge and technical skills of teaching, in addition to mastering the science or materials to be taught. Responsibility in giving guidance emphasizes the task of the teacher in providing assistance to students in solving problems it faces. In other words, religious education as effective way to fortify the younger generation now faced with the development of modernization, fortify themselves with noble morals. The last finding is explaining that government creates and enacts policies that enable people to know the latest information. Keywrods; Communication Technology, Community Religious Life, Aceh Singkil Regency